Monitoring and Controlling System to Artificial Habitat of Antlion (Myrmeleon Sp.) based Wireless Sensor Network - Fairuz Rahmadika; Aad hariyadi; Lis Diana Mustafa (Politeknik Negeri Malang, 2023)
Antlion habitat that breeders create currently does not use a system that can protect the habitat from changes in temperature and humidity. In addition, when they are about to be sold, breeders filter and sort the antlion one by one. Therefore, a system is made that can monitor and control changes in temperature and humidity as well as harvesting automatically through the application. This system is designed using a wireless sensor network with temperature and humidity sensors DHT22, IR MLX90614 with soft actuators and mist makers as well as loadcell sensors to trigger off the sieving motor connected to the Firebase database and interface Flutter application. Based on the results of testing the accuracy of temperature, humidity, infrared, and loadcell sensor readings, respectively, they are 98.07, 97.58%, 98.38%, and 98.78% with an average delay of 216,97ms can maintain temperature changes in the range 24-30? and humidity in the range 70-80% stably. And the average value of harvest time is 30.37 seconds with an average decrease in sand load of 56.7 grams when the harvesting mechanism is running.